Fine-grained hierarchical crop type classification from integrated hyperspectral EnMAP data and multispectral sentinel-2 time series: A large-scale dataset and dual-stream transformer method - Wenyuan Li; Shunlin Liang; Yuxiang Zhang; Liqin Liu; Keyan Chen; Yongzhe Chen; Han Ma; Jianglei Xu; Yichuan Ma; Shikang Guan; Zhenwei Shi (Remote Sensing of Environment, 2026)

Structure-activity relationship and salinity-driven degradation pathway and toxicity divergence of bromophenols during advanced reduction in VUV/sulfite system - Yawei Shi; Keyan Liu; Yan Wang; Ya Sun; Zonglin Pan; Mengqi Li; Guanghui Ding (Journal of Water Process Engineering, 2026)

Agglomeration under strain: Nonlinear dynamics of urban functional conflicts - Hongbo Zhao; Zeting Jia; Wenhui Yue; Yansui Liu; Qiyang Liu; Li Yue; Shaozhen Cao; Yilin Ma; Keyan Lu (Sustainable Cities and Society, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Identification of new virulence factors in Penicillium expansum via comparative transcriptomic analysis of three Penicillium species - Ting Liu; Keyan Zhao; Mengyang Xing; Yong Chen; Shiping Tian; Boqiang Li (Postharvest Biology and Technology, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Tracing sources and ecological risks: seasonal-spatial variations of potentially toxic element (PTE) pollution in marine sediments of Beibu Gulf - Zihan Bi; Yao Guan; Linshen Yang; Rongtao Ou; Yilu Gu; Huihua Wei; Xin Liu; Zezhuang Liu; Liping Tian; Keyan Xiao; Siyong Quan; Xuya Peng; et al. (Marine Pollution Bulletin, 2026)

An integrated framework combining deep learning and multicriteria decision-making for SDG-oriented urban low-carbon transition capacity assessment - Wentao Wang; Dezhi Li; Keyan Liu; Yongheng Zhao; Huan Zhou; Shenghua Zhou (Environmental Impact Assessment Review, 2026)

Rainfall shapes CO₂ emission and dissolved organic matter dynamics in a karst catchment: Controlling factors revealed by isotopic and molecular signatures - Jinfeng Ge; Yulin Qi; Yuanbi Yi; Chao Ma; Wenrui Yao; Xin Liu; Haoyang Wang; Keyan Li; Fu-Jun Yue; Tao Peng; Si-Liang Li (Water Research, 2026)

Lignin-intercalated WS2 with synergistic adsorption for efficiency lead removal - Baohua Liu; Xiangsheng Han; Keyan Yang; Jiankang Zhang; Hongzhen Cai (Bioresource Technology, 2026)

The Spring-Autumn and Warring States period coldness (400–350 BCE) contributed to the social unrest evidenced from coffin tree rings in southeastern China - Min Zhou; Zhongcai Xiao; Xin Jia; Xuanbo Wang; Liangsai Zhu; Feifei Zhou; Di Zhang; Zepeng Mei; Mengling Liu; Xinyuan Kong; Keyan Fang (Quaternary Science Reviews, 2025)

Innovative for farmland reclamation: Optimizing earthwork allocation and elevation in mining-induced subsidence - Zhuo Wang; Gensheng Li; Junjiang Liu; Keyan Guo; Honglin Liu; Tenghao Wang; Jinmao Ju; Junhui Zhang (Journal of Environmental Management, 2025)

MnFe2O4 coupled with MgAl-LDH for activation of periodate towards enhanced degradation of organic pollutants in water - Ya Sun; Chang Ma; Yawei Shi; Zonglin Pan; Yumei Xing; Yan Wang; Keyan Liu; Guanghui Ding (Journal of Water Process Engineering, 2025)

Associations of long-term exposure to fine particulate matter and its components with ovarian aging: Evidence from a cross-sectional study in China - Zifeng Cao; Xinyi Wu; Hongyuan Liu; Keyan Xu; Yehuan Yang; Manting Yang; Daimin Wei; Shidou Zhao; Xue Jiao; Qi Zhao; Ruimin Zheng; Yingying Qin; et al. (Journal of Hazardous Materials, 2025)

The first temperature reconstruction based on tree-ring blue intensity in the Qinling Mountains - Mei Xie; Qiufang Cai; Yu Liu; Keyan Fang; Qiuyue Zhou; Meng Ren; Kebayier Meng; Qiang Li; Changfeng Sun; Huiming Song; Dan Chen; Yufei Chen (Dendrochronologia, 2025)

Enhancing Botrytis cinerea resistance in strawberry preservation with non-contact functionalized chitosan-Cinnamaldehyde composite films - Hongsu Wang; Qianliao Zhou; Keyan Pan; Lu Liu; Xiaodi Niu (Food Chemistry, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Structure and dynamics of stationary fronts in an angled river plume - Keyan Liu; Jiaxue Wu; Huan Liu; Xiangyu Li; Zhenkun Lin; Leiping Ye (Estuarine, Coastal and Shelf Science, 2025)

Flexible MXene-functionalized composite phase change film with dual-mode of solar-thermal conversion and infrared stealth - Keyan Sun; Fanmu Meng; Xinyu Zhang; Huimin Yan; Hanqing Liu; Quan Shi (Chemical Engineering Journal, 2025)

Boosting chlorobenzene oxidation over MIL-101(Cr) derived CrOx catalysts: The stepwise regulation of CrOx clusters and oxygen species by calcination atmospheres - Boqiong Jiang; Jun Liu; Keyan Wei; Hanfeng Lu; Xiaole Weng; Jingyi Han; Yi Zhang; Shaocai Yu; Yuhai Sun (Journal of Hazardous Materials, 2025)

Quantitative Risk Assessment of Wellbore Collapse of Inclined Wells in Formations with Anisotropic Rock Strengths - Tianshou Ma; Keyan Liu; Yi Qiu; Jinhua Liu; Dmitriy A. Martyushev; P. G. Ranjith (Rock Mechanics and Rock Engineering, 2025)

Insights into the differences in meat quality among different sheep breeds in the Qilian Mountains from the perspective of metabolomics and transcriptomics - Keyan Ma; Juanjuan Song; Dengpan Li; Zilong Liu; Chunhui Wang; Taotao Li; Youji Ma (Food Bioscience, 2025)

Exposure of functional group from hyperbranched precursor to arrange SiOC phase for lithium-ion batteries - Quanhui Wu; Pengfei Wu; Huibin Tu; Sen Mi; Zhenpu Zhang; Keyan Song; Anhua Liu (Chemical Engineering Journal, 2025)

A novel reservoir dispatching rules extraction framework based on hybrid embedding informer - Shuai Liu; Hui Qin; Zhengyang Tang; Keyan Shen; Xu Yang; Zhiwei Zheng; Yuhua Qu; Zhiwei Jia (Journal of Hydrology, 2024)

Deciphering the transfer of hydroclimate signals to tree-ring δ18O using a proxy system model in East Asia's Meiyu region - Yesi Zhao; Huayu Lu; Keyan Fang; Peng Zhang; Deliang Chen; Achim Bräuning; Jussi Grießinger; Bao Yang; Chenghong Liang; Hongyan Zhang; Yiqian Sun; Qing Jin; et al. (Chemical Geology, 2024)

Identification of Geochemical Anomalies Using an End-to-End Transformer - Shuyan Yu; Hao Deng; Zhankun Liu; Jin Chen; Keyan Xiao; Xiancheng Mao (Natural Resources Research, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

Investigation on the anisotropy of meso-mechanical properties of shale rock using micro-indentation - Tianshou Ma; Keyan Liu; Xue Su; Ping Chen; P. G. Ranjith; Dmitriy A. Martyushev (Bulletin of Engineering Geology and the Environment, 2024)

ZYY-B-2, a novel ALK inhibitor, overcomes resistance to ceritinib by inhibiting P-gp function and induces apoptosis through mitochondrial pathway in ceritinib-resistant H2228 cells - Ying Gao; Tong Liu; Jingang Liu; Yuying Yang; Keyan Sun; Zengqiang Li; Xin Zhai; Daiying Zuo (Chemico-Biological Interactions, 2023)

Weakened western Pacific teleconnection pattern caused a decrease in spring persistent rainfall in north of 26°N over Southeast China - Yao Chen; Chongqing Wang; Feifei Zhou; Shixiong Jiang; Xi Li; Sunxian Weng; Xinyuan Wan; Rongyang Xiao; Qiang Liu; Keyan Fang (International Journal of Climatology, 2023)
The spring persistent rainfall (SPR) is a unique synoptic and climatic phenomenon before the onset of the Asian summer monsoon over Southeast China (SEC). The warming climate has caused notable interdecadal changes of various climate systems, such as the Asian summer monsoon. However, it is still unclear whether there is a regime shift within the SPR band. To fill this knowledge gap, the boreal spring (March–May) rainfall data across SEC from the Climate Research Unit TS 4.05 are used herein to reveal its spatio‐temporal variations for 1951–2019 with the empirical orthogonal function (EOF) analysis. The EOF1 pattern exhibits a spatial monotonic variability of the SPR over SEC, which is jointly impacted by the El Niño‐Southern Oscillation and the Arctic Oscillation. The EOF2 pattern, a south–north dipole pattern, highlights a marked decrease (increase) of the SPR approximately to north (south) of the 26°N. We find that the decrease in the northern SPR band is closely modulated by western Pacific teleconnection pattern (WPP). Recent weakening WPP is coincident with a decline of the East Asian subtropical jet over this area, causing anomalous descending motions and thus accounts for persistent decline of the SPR over north of 26°N.

Dexmedetomidine alleviates cerebral ischemia-reperfusion injury via inhibiting autophagy through PI3K/Akt/mTOR pathway - Jianli Li; Keyan Wang; Meinv Liu; Jinhua He; Huanhuan Zhang; Huan Liu (Journal of Molecular Histology, 2023)

Mechanism of the reduced allergenicity of shrimp (Macrobrachium nipponense) by combined thermal/pressure processing: Insight into variations in protein structure, gastrointestinal digestion and immunodominant linear epitopes - Kexin Liu; Songyi Lin; Yao Liu; Shan Wang; Qiaozhen Liu; Keyan Sun; Na Sun (Food Chemistry, 2023)

Thiol “click” chromene mediated cascade reaction forming coumarin for in-situ imaging of thiol flux in drug-induced liver injury - Yutao Yang; Keyan Zhou; Ming Ma; Hongmei Liu; Ming Jin; Caixia Yin; Shuxiang Wang; Jinchao Zhang (Chemical Engineering Journal, 2023)

An Improved GWR Approach for Exploring the Anisotropic Influence of Ore-Controlling Factors on Mineralization in 3D Space - Jixian Huang; Xiancheng Mao; Hao Deng; Zhankun Liu; Jin Chen; Keyan Xiao (Natural Resources Research, 2022)

Estimation of the Interaction Between Groundwater and Surface Water Based on Flow Routing Using an Improved Nonlinear Muskingum-Cunge Method - Chengpeng Lu; Keyan Ji; Wanjie Wang; Yong Zhang; Tema Koketso Ealotswe; Wei Qin; Jiayun Lu; Bo Liu; Longcang Shu (Water Resources Management, 2021)

Reinvestigation of the substrate specificity of a reverse prenyltransferase NotF from Aspergillus sp. MF297-2 - Keyan Yang; Shu-Ming Li; Xiaoqing Liu; Aili Fan (Archives of Microbiology, 2020)

Regeneration of Fe II /Fe III complex from NO chelating absorption by microbial fuel cell - Qiang Liu; Keyan Yu; Peng Yi; Weimin Cao; Xueping Chen; Xiaolei Zhang (Environmental Science and Pollution Research, 2019)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Abrupt vegetation shifts caused by gradual climate changes in central Asia during the Holocene - Yan Zhao; YaoLiang Liu; ZhengTang Guo; KeYan Fang; Quan Li; XianYong Cao (Science China Earth Sciences, 2017)

Climate–growth relationships of Schrenk spruce (Picea schrenkiana) along an altitudinal gradient in the western Tianshan mountains, northwest China - Yuxia Huo; Xiaohua Gou; Wenhuo Liu; Jinbao Li; Fen Zhang; Keyan Fang (Trees, 2017)

Precipitation variability during the past 400 years in the Xiaolong Mountain (central China) inferred from tree rings - Keyan Fang; Xiaohua Gou; Fahu Chen; David Frank; Changzhi Liu; Jinbao Li; Miklos Kazmer (Climate Dynamics, 2012)

Tree growth and time-varying climate response along altitudinal transects in central China - Keyan Fang; Xiaohua Gou; Fahu Chen; Jinbao Li; Rosanne D’Arrigo; Edward Cook; Tao Yang; Wenhuo Liu; Fen Zhang (European Journal of Forest Research, 2010)

Drought reconstruction in the Qilian Mountains over the last two centuries and its implications for large-scale moisture patterns - Wenhuo Liu; Xiaohua Gou; Meixue Yang; Yong Zhang; Keyan Fang; Tao Yang; Liya Jin (Advances in Atmospheric Sciences, 2009)